Dry and wet season polymorphism in the butterflies, Melanitis leda and Mycalesis mineus (Satyridae: Lepidoptera) - Islam, ATMF; Razzak, MA; Islam, MH; Saifullah, ASM; Endo, K; Yamanaka, Akira (University Journal of Zoology, Rajshahi University, 2012)
A field survey of butterflies was carried out in different areas of deciduous forests at Kaliakyar, Gazipur, during January-December, 2008. Seven species of satyrid butterflies were collected and two species, Melanitis leda and Mycalesis mineus were found to exhibit dry and wet season polymorphism. The dry season forms (DSFs) and wet season forms (WSFs) of the both species were distinguished by their upperside and underside wing patterns. The DSFs occurred only in the drier period (November to February) when day length was shorter than 12 hrs. at lower temperatures (24.1-20.6°C). Both the species of butterflies of the wetter period (March - October) were predominant of the WSF when day length was longer than 12 hrs. at higher temperatures (26.8-27.6°C). The fluctuations in the number of seasonal forms of M. leda and M. mineus were higher in DSF than those of WSF. The transition of DSF to WSF and WSF to DSF of M. leda was found to occur around the end of April and the early of September, respectively. But the turnover of DSF to WSF occurred around the early March and the turnover of WSF to DSF in October in M. mineus. Key word: Butterflies; seasons; polymorphism; Melanitis leda; Mycalesis mineus DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9463 UJZRU 2010; 29(1): 33-39